Women’s Roles in Puritan Society as reflected in Nathaniel Hawthorne’s The Scarlett Letter - Rina Marliana; Nihla Afdaliah; Rismawati Rismawati (Hasanuddin University, 2020)
Literature has a function as reflection or as mirror of the society. The Scarlett Letter by Nathaniel Hawthorne is one of literary works that could reflect the social condition or phenomena of the Puritan society in America. This research was a descriptive qualitative research. The data were collected by using library research and it was analyzed by applying sociological approach proposed by Swingewood (1972) who revealed three classifications of sociology of literature. In this case, the researcher focused on the classification of sociology as the mirror of age. The result of this research showed that the important women’s roles in puritan society is teaching their children about the scripture